2022
DOI: 10.1039/d1bm02021h
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence of oncofetal antigen and TLR-9 agonist co-delivery by alginate nanovaccines for liver cancer immunotherapy

Abstract: Liver cancer is the most common malignant tumor and liver cancer immunotherapy has been one of the research hotspots. To induce antigen-specific antitumor immune responses against liver cancer, we developed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Neutrophils are frequently dominant and are linked to immunological escape from tumors ( 18 ). Consequently, these findings imply that FCN2 may suppress the HCC tumor immune response by favorably regulating neutrophils ( 19 , 20 ), eosinophils ( 21 ), NK cells ( 22 – 24 ), Tcm ( 25 ), and DCs ( 26 28 ) and negatively regulating Th2 ( 29 – 31 ) in tumors.…”
Section: Discussionmentioning
confidence: 93%
“…Neutrophils are frequently dominant and are linked to immunological escape from tumors ( 18 ). Consequently, these findings imply that FCN2 may suppress the HCC tumor immune response by favorably regulating neutrophils ( 19 , 20 ), eosinophils ( 21 ), NK cells ( 22 – 24 ), Tcm ( 25 ), and DCs ( 26 28 ) and negatively regulating Th2 ( 29 – 31 ) in tumors.…”
Section: Discussionmentioning
confidence: 93%
“…The enrichment analyses showed that the signature was associated with immune functions. Immunotherapy has currently been applied for the treatment of a variety of tumor types, including lung cancer 42 , melanoma 43 , cervical cancer 44 and liver cancer 45 . Immune checkpoints, for instance programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), have the ability to encourage anticancer immune function 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver cancer immunotherapy has been the hotspot in liver cancer treatment. To induce anti-tumor immune responses, Pei et al ( Pei et al, 2022 ) designed nanovaccines consisting of polyanionic alginate (ALG) and polycationic polyethyleneimine (PEI) to co-deliver glypican-3 peptide antigens and unmethylated cytosine-phosphate-guanine adjuvants. The particle size of nanovaccines was 218 nm, and the zeta potential was 21 mV.…”
Section: Polymer-based Nanocarriers For Co-deliverymentioning
confidence: 99%
“…Researchers extracted the vesicles secreted by cancer cells to prepare drug delivery carriers, which effectively delivered drugs to cancer cells via direct fusion with cancer cells. Li et al (Li H. et al, 2022) used extracellular vesicles (EVs) as natural drug carriers to codeliver DOX and ronidamine (LND), a chemical sensitizer, for the treatment of lung cancer. They found that different centrifugal forces could affect the size of EVs, thus, affecting anti-cancer efficiency, and their results showed that smaller EVs had higher anti-cancer efficiency.…”
Section: Other Lipid-based Carriersmentioning
confidence: 99%